The Differences in VAS Values Before and After Physiotherapy in Low Back Pain Patients at the Orthopedic Polyclinic, Santa Anna Hospital, Kendari - Wa Ode Nur Dian Al Janna; Asriati; Mario Polo Widjaya (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Low Back Pain (LBP) is an unpleasant condition accompanied by activity limitations caused by pain when moving. Physiotherapy conducted on LBP patients is intended to reduce pain and restore functional abilities. This study aims to determine the differences in VAS values ​​before and after physiotherapy conducted on LBP patients at the Orthopedic Poly of Santa Anna Kendari Hospital. Methods: This observational analytical study used a cross-sectional approach. The study used secondary data in the form of medical records from 30 LBP patients who were undergoing physiotherapy. The observed dependent variable was the VAS value before physiotherapy and the independent variable observed was the VAS value after physiotherapy. The data analysis used the Wilcoxon statistical test. If the value was p≤0.05. Results: The Wilcoxon analysis test showed that there was a significant difference in VAS values ​​(p≤0.05) before and after physiotherapy conducted on LBP patients at the Orthopedic Poly of Santa Anna Kendari Hospital. Conclusion: There is a difference between the VAS values ​​before and after physiotherapy conducted on LBP patients at the Orthopedic Poly of Santa Anna Kendari Hospital.